ANALISIS KEMAMPUAN INTELEKTUAN DOSEN DAN METODE MENGAJAR MEMPENGARUHI MOTIVASI BELAJAR BAHASA INGGRIS MAHASISWA STIE AMKOP MAKASSAR - Firman Firman (AkMen JURNAL ILMIAH, 2015)
The results reveal that the value of r2 is 0,292 or (29.2%) means that the variance of the dependent variable that can be explained independent of 29.2%, while 71.8% is explained by other variables not examined in this study